TINGKAT PENCEMARAN LOGAM Cd, Fe, Cr DAN Cu AIR SUMUR GALI DI Eks-TPA TALANG GULO KOTA JAMBI - Gusri, Lailal; Yanova, Shally; Gayatri, Indah (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Former solid waste disposal at Talang Gulo TPA Jambi City implements a waste management system using a controlled landfill. Leachate and rainwater absorb into the soil and accumulate to become polluted groundwater. Furthermore, the polluted water flows into the dug well water and can reduce the quality of the dug well water. The aim of this study is to determine the heavy metal pollution index of residents' dug well water and the influence of the distance between the ex-TPA and dug well water. This research method is purposive sampling based on the distance of heavy metal sample points, namely 70 m, 230 m and 300 m. Sample analysis used an Atomic Absorption Spectrophometer (AAS) in the laboratory. The results were classed and indexed (C/P), the groundwater was very lightly contaminated with Cd (<0.1), heavily contaminated with Fe (0.51-0.75), very lightly contaminated with Cr (<0.1), and moderately contaminated with Cu (0.26-0.50). Based on the R value of the four metals, it shows that there was a very high influence between the distance between the well water sample and the former solid waste disposal leachate product.